OP0033 Classification Criteria for Systemic Sclerosis: Preliminary Results. (23rd January 2014) - Van Den Hoogen, F.; Khanna, D.; Fransen, J.; Johnson, S. R.; Baron, M.; Tyndall, A.; Matucci, M.; Naden, R.; Pope, J.
Abstract : Background: The existing 1980 classification criteria for systemic sclerosis (SSc) are suboptimal for patients with early SSc and some patients with limited cutaneous SSc (lcSSc) where an important subset do not meet those criteria. Objectives: To develop and test new classification criteria for SSc by a joint EULAR and ACR committee. Methods: Delphi exercises and a nominal group technique were used to create a set of potential items for classification of SSc. Twenty cases were prospectively collected to represent the spectrum of SSc (low probability to high probability) which were ranked by SSc experts and conjoint analysis (1000 Minds®) was used to assign weights to the items and reduce the number of items. Experts agreed that all patients with sclerodactyly and scleroderma skin involvement proximal to the MCPs were considered SSc; patients with skin involvement due another scleroderma-like disorder (e.g. scleromyxedema) or skin thickening sparing the fingers were not regarded to have SSc. The provisional classification system was tested in a random sample of SSc cases and controls of 100 from North America and 100 from Europe (derivation sample). The system was simplified and calibrated to real cases. The classification system was re-analyzed in another sample of SSc cases and controls (validation set; n=405). Results: The table provides the final items with the proposed weights. Only the maximum score in each domain is counted. A cut-off of >= 9 (out of 19) had a sensitivity of 91% and specificity of 92% in the validation cohort (n=405). The sensitivity and specificity of the former 1980 ARA criteria in this database were 75% and 72%, respectively. These results are preliminary and not yet approved by the organizational sponsors. Conclusions: The preliminary results of the classification criteria for SSc performed better than 1980 Preliminary ARA Criteria for SSc. These criteria can be endorsed for epidemiological studies and clinical trials after approval by ACR and EULAR. Disclosure of Interest: None Declared